Internalization of Islamic Values Through PAI Learning in Forming Students' Social Awareness and Religiosity Based on Islamic Boarding School - Zaenol Fajri; Liya Aminah Basmah Tauhidah (BASICA, 2026)
The loss of students' social consciousness and religiosity resulting from globalization and the inadequate teaching of Islamic Religious Education (PAI), which still emphasizes cognitive aspects, is the driving force behind this study. Thus, the purpose of this study is to characterize how Islamic boarding school-based pupils in grade 1A of MI At-Taqwa Bondowoso internalize Islamic values through PAI learning, thereby shaping their social awareness and religiosity. This study combined a case study methodology with a qualitative approach. Observation, in-depth interviews, and documentation using tools such as observation sheets, interview guides, and learning documents were used to collect data. Data reduction, data presentation, and conclusion drawing were used in data analysis, and triangulation was used to assess the validity of the results. The findings show that learning, habituation, and teacher role models all contribute to the methodical and integrative process of internalizing Islamic beliefs. Students' religious and social consciousness can be raised through practices such as positive social interactions, contextual approaches, habitual worship, and behavioral reinforcement. Despite challenges such as variations in student characteristics and time constraints, the Islamic boarding school's religious atmosphere and teachers' role as role models are important supportive aspects. This study offers implications for the significance of including content, routines, and role models in the learning process. It advances the development of holistic, character-based Islamic Religious Education (PAI) instruction. In summary, pupils' general character is effectively shaped by internalizing Islamic ideals. To maximize the process of internalizing values, it is advised that educators create creative strategies, schools fortify their religious culture, and improve cooperation with parents.